2013
DOI: 10.1007/s11302-013-9367-2
|View full text |Cite
|
Sign up to set email alerts
|

Sensory–sympathetic coupling in superior cervical ganglia after myocardial ischemic injury facilitates sympathoexcitatory action via P2X7 receptor

Abstract: P2X receptors participate in cardiovascular regulation and disease. After myocardial ischemic injury, sensorysympathetic coupling between rat cervical DRG nerves and superior cervical ganglia (SCG) facilitated sympathoexcitatory action via P2X 7 receptor. The results showed that after myocardial ischemic injury, the systolic blood pressure, heart rate, serum cardiac enzymes, IL-6, and TNF-α were increased, while the levels of P2X 7 mRNA and protein in SCG were also upregulated. However, these alterations dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…Previous studies in our laboratory showed that the upregulation of the P2X 3 , P2X 2/3 , and P2X 7 receptors in the stellate ganglia (SG) and superior cervical ganglia (SCG) after MI injury resulted in increased blood pressure and HR by strengthening the activity of the sympathetic postganglionic neurons [15,[18][19][20][21][22][23][24][25][26][27][28]. Our works also showed that P2X 3 , P2X 2/3 , or P2X 7 antagonists decreased the elevated SBP and HR and alleviated the arrhythmia induced by myocardial ischemia [15,[18][19][20][21][22][23][24][25][26][27][28][29]. NONRATT021972 is a lncRNA [30] [http://www.noncode.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous studies in our laboratory showed that the upregulation of the P2X 3 , P2X 2/3 , and P2X 7 receptors in the stellate ganglia (SG) and superior cervical ganglia (SCG) after MI injury resulted in increased blood pressure and HR by strengthening the activity of the sympathetic postganglionic neurons [15,[18][19][20][21][22][23][24][25][26][27][28]. Our works also showed that P2X 3 , P2X 2/3 , or P2X 7 antagonists decreased the elevated SBP and HR and alleviated the arrhythmia induced by myocardial ischemia [15,[18][19][20][21][22][23][24][25][26][27][28][29]. NONRATT021972 is a lncRNA [30] [http://www.noncode.…”
Section: Introductionsupporting
confidence: 61%
“…b The histogram shows the normalized, mean peak current (mean ± S, n = 12, **P < 0.01, compared to the con group; ## P < 0.01 vs the MI group). NONRATT021972 siRNA decreased the BzATP-induced currents in HEK293 cells expressing the hP2X 7 receptor by an increase in blood pressure and sympathetic nerve activity [14,19,24,29]. Previous data from our laboratory showed that the serum ATP concentration was increased after the MI injury [32].…”
Section: Discussionmentioning
confidence: 88%
“…There is up-regulation of P2X7R in rat superior cervical ganglia (SCG) after myocardial ischaemic injury [589]. Sensory-sympathetic coupling in SCG after myocardial ischaemic injury facilitates sympathoexcitatory action via upregulated P2X7R [590]. The P2X7R antagonist brilliant blue G acting on stellate ganglia prevented the increased sympathoexcitatory reflex via sensory-sympathetic coupling induced by myocardial ischaemic injury [591].…”
Section: Ischaemiamentioning
confidence: 99%
“…Evidence has indicated that the P2X7 receptor was involved in the process of inflammatory response and release of inflammatory mediators [20,21]. Our previous studies also showed that the P2X7 receptor played a major role in the transmission of inflammatory signals and contributed to the pathological process of sympathetic injury [6,10,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 77%
“…This finding suggests nc021972 may be involved in the pathophysiologic processes related to the sympathetic neuron under the setting of diabetes. Our previous studies have shown that the P2X7 receptor was implicated in the pathological injury of sympathetic nerves [6,10,[22][23][24][25]. The aim of the study was to examine the effects of nc021972 small interference RNA (siRNA) on the P2X7 receptor and its possible role in neuroinflammation induced by elevated glucose and FFAs in PC12 cells.…”
Section: Introductionmentioning
confidence: 99%